DETECTION OF BUILDING VIBRATIONS APPLYNG PHOTO DEFLECTION RESPONSE - Valera, Aníbal (2008)
This paper presents the results of evaluating the vibration of a Building (Science Building / UNI) based on the Method of Laser Photo deflection. The evaluated vibrations of the building were, respectively, of spontaneous nature (produced by wind, automobile traffic, seismic waves) and induced (micro vibrations excited by sound waves). The procedure allowed us,to evaluate the following cases: a-A resonant effect occurred in the principal building Hall, b-Correlation of spontaneous and induced vibrations in the building, c-Detection and evaluation of building vibrations generated by Seismic waves.